Effects of the coronavirus disease 2019 pandemic and the policy response on childhood obesity risk factors: Gender and sex differences and recommendations for research. (28th June 2021) - Knebusch, Veronika; Williams, Julianne; Yordi Aguirre, Isabel; Weber, Martin W.; Rakovac, Ivo; Breda, João
Summary: Childhood obesity is a public health concern globally, with generally higher prevalence rates in boys compared to girls. Although biological sex is an important determinant, gender roles and norms influence the exposure and vulnerability to risk factors for noncommunicable diseases. Norms and roles might be reinforced or change due to coronavirus disease 2019 (COVID‐19) related measures as well as the exposure to risk factors for childhood obesity. COVID‐19 related changes, such as home confinement, influence a child's risk of obesity. Using Dahlgren and Whitehead's model of the main determinants of health, this paper aims to provide a roadmap for future research on sex, gender, and childhood obesity during the time of COVID‐19. It examines how COVID‐19 has led to important changes in children's general socioeconomic, cultural, and environmental conditions, social and community networks, and individual lifestyle factors and how these may affect a child's risk for obesity. It focuses on the influence of gender and sex and outlines key considerations and indicators to examine in future studies concerned with promoting health and gender equity and equality. We need to understand the differential impact of COVID‐19 related measures on girls' and boys' risk for obesity to adequately react with preventive measures, policies, and programs.